The Implication Inferred from the Expression of Small Heat-Shock Protein Genes in Dinoflagellate Resting Cysts Buried in Marine Sediment - Yunyan Deng; Fengting Li; Zhangxi Hu; Caixia Yue; Ying Zhong Tang (Diversity, 2021)
Dinoflagellates are unicellular eukaryotic microalgae, occupying pivotal niches in aquatic ecosystems with great ecological, biological, and economic significance. Small heat shock proteins (sHsps) are the most omnipresent, but the least conserved, family of molecular chaperones found in all domains of life. Although their common name (small Hsp) implies to exclusively stress their heat shock-responsive function, many sHsps in fact engage in a variety of physiological processes, from cell growth and proliferation to embryogenesis, development, differentiation, apoptosis, and even to human disease prevention. Recent years have greatly expanded our understanding of sHsps in higher plants; however, comprehensive study aiming to delineate the composition and expression pattern of dinoflagellate sHsp gene family has not yet been performed. In this study, we constructed dinoflagellate-specific environmental cDNA library from marine sediment and sequenced using the third-generation sequencing technique. Screening of sHsp genes from the library returned 13 entries with complete coding regions, which were considered to be transcriptionally activated in the natural community of dinoflagellate resting cysts. All the 13 dinoflagellate sHsps consisted of a solely characteristic α-crystallin domain, covering 88–123 amino acid residues with the typical A-X-X-X-N-G-V-L motif, flanked by variable N- and C-terminal extensions. Multiple alignment revealed considerable amino acid divergence (~26.7% average similarity) among them. An unexpected close relationship was revealed between dinoflagellate and green algal sHsps in the phylogenetic tree, seemingly reflecting a close evolutionary relationship of these sHsps themselves. We confirmed that sHsp mRNAs are expressed during dormancy of the resting cyst assemblages of dinoflagellates that were buried in marine sediment, which raised the possibility that the sHsp expression is part of the machinery of maintaining the dormancy or/and the adaptation to ambient conditions of dinoflagellate resting cysts. Our results, although preliminary, gained an important glance on the universal presence of sHsps in dinoflagellates and their active expressions in the assemblage of resting cysts that were buried in the marine sediment. The essentiality of sHsps functioning in resting cysts necessitate more intensive and extensive investigations on all possible functions of Hsps in dinoflagellates, a group of protists with vital ecological and biological importance.